Fabrication of the antimicrobial sachet by encapsulation of peppermint essential oil in active packaging of strawberry fruit. Issue 12 (5th October 2022) - Amiri, Azam; Sourestani, Mohammad Mahmoodi; Mortazavi, Seyed Mohammad Hassan; Kiasat, Ali Reza; Ramezani, Zahra
Abstract: The anti‐microbial property‐based packaging system is able to destroy and eliminate the contaminants and pathogenic microorganisms, which spoil the food. In this study, sachets were prepared by an active packaging system using starch‐based microcellular foam loaded with peppermint essential oil (SMF‐PEO). The produced SMF was used to make sachets loaded with PEO and then placed on the upper part of the strawberry package. Qualitative and biochemical traits of the strawberry fruits, such as weight loss percentage, vitamin C, phenolic substances, antioxidant capacity, anthocyanin, malondialdehyde, hydrogen peroxide content, microbial load, and antioxidant enzymes activity, were evaluated. Results of the gas chromatography confirmed EO release until the end of the fourth day of the fruit storage. Fourier‐transform infrared spectroscopy spectra showed the porosity of the SMF and the loading of PEO in its pores. Total phenol and antioxidant activity decreased during storage. At the end of storage, the most total antioxidant activity (29.04 iron II mol g −1 ) was found in packaged fruits with sachet, whereas the most anthocyanin (896 mg kg −1 ) was found in control. At the end of the storage period, the treated fruits showed a greater catalase (1660 U kg −1 ) and phenylalanine ammonia‐lyase (1626.6 U kg −1 ) activity. Packaged fruits with sachet had lower microbial load, total mesophilic bacteria in control and treated samples was 3.7 and 1.7 Log CFU g −1 in end during storage. At the end of storage, the total yeast + mold in treated and control fruits was 1.3 and 1.57 Log CFU g −1, respectively. Practical applications: The sachets loaded with PEO increased activity of enzymes and the decreased amount of malondialdehyde have a positive effect on increasing the shelf life of strawberry fruits and are efficient enough to reduce microbial load. Due to the inexpensiveness and degradability of starch, SMF is a suitable system for PEO loading.